ADE Bundles Over ADE Singular Surfaces and Flag Varieties of ADE Type. (20th February 2017) - Chen, Yunxia; Leung, Naichung Conan
Abstract: Based on the Brieskorn–Slodowy–Grothendieck diagram, we write the holomorphic structures (or filtrations) of the ADE Lie algebra bundles over the corresponding type ADE flag varieties, over the cotangent bundles of these flag varieties, and over the corresponding type ADE singular surfaces. The main tool is the cohomology of line bundles over flag varieties and their cotangent bundles.